(untitled) (Research, Society and Development, 2025)
The following documentary article describes a pedagogical vision on Maria Montessori (1870-1952), with a focus on intercultural context (Snyder, 2019). Her methodology revolves around the educational context of children from disadvantaged backgrounds in Rome, Italy. With her scientific legacy extending as far as the Netherlands, India, France, Mexico and the United States. Montessori addressed the emergencies of her time period, the First and Second World War. Although there was a strong encounter with other cultures, its interculturality was never discussed. However, its cosmic lesson: the biological and cultural development of the subject concerns perpetual spaces of solidarity. The current social condition of the world outlines intercultural conceptual frameworks. This work analyzes this issue from Montessori’s pedagogical perspective, the current impact within the guidelines of Italian public education systems and is concluded with Montessori’s intercultural vision in relation to the pedagogical issues of the 21st century.